Kinetic study of photoreaction of triarylphosphines by laser flash photolysis time-resolved UV-VIS spectroscopy. (2nd January 2016) - Yasui, Shinro; Kobayashi, Shinjiro; Mishima, Masaaki
GRAPHICAL ABSTRACT: Abstract: Laser flash photolysis (LFP) time-resolved UV–VIS (TRUV) spectroscopy was carried out on the acetonitrile solution of triarylphosphines, Ar3 P, in an oxygen, air, or argon atmosphere. The transient absorption most likely from a triarylphosphine radical cation, Ar3 P ·+, appeared on the TRUV, which disappeared with the rate depending on the concentration of O2 .